Garciniaxanthone E and 12b-Hydroxy-des-D-garcigerrin A from The Tree Bark Garcinia dulcis and their Inhibitory Properties against Receptor Tyrosine Kinases - Kurniadewi, Fera; Aqilah, Amadita Shafa; Kartika, Irma Ratna; Nurjayadi, Muktiningsih; Hermawati, Elvira; Danova, Ade (Syarif Hidayatullah State Islamic University, 2024)
Two xanthone derivatives, garciniaxanthone E (1) and 12b-Hydroxy-des-D-garcigerrin A (2) have been isolated from ethyl acetate extract of the tree bark of Garcinia dulcis. The Ultraviolet (UV), Infrared (IR), Nuclear Magnetic Resonance (NMR), and Mass Spectrometry (MS) data analysis elucidated the structure of the isolated compounds. This study represents the first evaluation of compounds 1 and 2 in terms of their efficacy against receptor tyrosine kinases. The results showed that compound 1 exhibited weak activity with 12% inhibition against Insulin Receptor (InsR), while compound 2 showed moderate activity with 29% inhibition against epidermal growth factor receptor (EGFR). A molecular docking study targeting EGFR-TK suggests that the hydroxyl group at C-4 on compound 2 can be demolished to raise the inhibitory activity in future research.